Nurettin Topçu’da din-kültür ilişkisi ve Anadoluculuk kavramı - Özdemir, Gül Deniz (My University, 2003)
Nurettin Topçu gerek felsefi alandaki ve gerekse din, toplum, iktisat ve eğitime dair görüşleriyle son dönem Türk düşün tarihinin en renkli simalarından biri olmuştur Bu tezde Topçu'nun kültür anlayışındaki dini düşünce ifade edilmeye çalışılmıştır. Bu sebepten öncelikle genel manada kültür kavramı üzerinde durulmuş ve insan ürünü olan bu birikimin büyük ölçüde inanç, ideoloji ve tutumlarca şekillendiği tespit edilmiştir. Bundan sonra sırasıyla N. Topçu'nun kültür ve din anlayışı irdelenerek dinin kültüre verdiği anlam ortaya konmuştur. Son bölümde Türk-İslam sentezi olarak değerlendirilen Anadoluculuk düşüncesinde Topçu'nun özel bir yere sahip olduğu belirtilmektedir. Bu sebeple Anadoluculuk düşüncesinin Topçu için daha geniş bir platformda ele alınması gerekliliği ifade edilerek bu platform din-kültür sentezi olarak nitelendirilmiştir. Name : Gül Deniz Surname : Özdemir Field : Teology Programme : Philosophy and Religious Sciences Kind of Thesis and Date : Master and İstanbul 2003 Counsultant of Thesis : Yrd. Doç. Dr. Ali Coşkun Religion, Culture, Anatolaism

THE RELATION BETWEEN RELIGION- CULTURE AND ANATOLIASM Nurettin Topçu is one of the famous thinkers in Turkish thought history, not only has his own views in philosophical field but alsa has thoughts concerning religion, society, economy and education. In this thesis I tried to explain the religous thought in Topçu's culture concept. For this reason, firs of all, I stressed on culture concept in general, which is product of mankind and I tried to determine that It was formed mostly by beliefs, ideologies and behaviors. In the second section of my thesis, I expased the meaning which religion added to culture by searching sense of culture and religion according to Nurettin Topçu. In last section of my thesis, I stressed that Nurettin Topçu has a special place in Anatoliasm, called as a synthesis of Turk-Islam. In this connection, I expressed the necessity of dealing with Anatoliasm on a wide platform, which is determined as a synthesis of Turk-Islam, especially for Nurettin Topçu.
Keywords: Din; İslam Dini; Kültür